The Correlation Between Knowledge of Medical Career Preference and Academic Motivation (A Study in School of Medicine, Faculty of Medicine Sebelas Maret University Surakarta) - Utari Nur Alifah; Rohmaningtyas Hidayah Setyaningrum; . Maryani (Nexus Pendidikan Kedokteran dan Kesehatan, 2016)
Introduction: Academic motivation is the most important factor in affecting academic achievement in medical education. Career in medicine that divided into clinical and non-clinical career is the output of medical education. Knowledge of medical career preferences can be obtained from information during education process. This study aims to investigate the correlation between knowledge of medical career preference and academic motivation in medical student of Sebelas Maret University. Methods: This study was an observational analytic with cross sectional approach. Subjects were 147 preclinical medical students in Sebelas Maret University using stratified random sampling. Knowledge of medical career preferences data was collected using valid and reliable questionnaire. Academic motivation data was collected using Academic Motivation Scale. Data were analyzed with Spearman correlation test. Results: The lowest average score of knowledge of medical career preferences was the first year student and the highest was the final year student. The lowest average score of academic motivation was the second year student. The Spearman correlation test showed a positive correlation (r=0,077) and statistically insignificant (p=0,355) between knowledge of medical career preference and academic motivation. Conclusion: There is a very low positive correlation and statistically insignificant between knowledge of medical career preference and academic motivation in medical student of Sebelas Maret University. Keywords: Academic motivation, knowledge of medical career preference, medical career.